2009
DOI: 10.1158/0008-5472.can-08-2110
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Ribosylation Factor 6 Regulates Glioma Cell Invasion through the IQ-Domain GTPase-Activating Protein 1-Rac1–Mediated Pathway

Abstract: A common pathobiological feature of malignant gliomas is the insidious infiltration of single tumor cells into the brain parenchyma, rendering these deadly tumors virtually incurable with available therapies. In this study, we report that ADP-ribosylation factor 6 (ARF6), a Ras superfamily small GTPase, is abundantly expressed in invasive human glioma cells. Cellular depletion of ARF6 by small interfering RNA decreased Rac1 activation, impaired HGF-stimulated and serum-stimulated glioma cell migration in vitro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 35 publications
5
90
0
Order By: Relevance
“…Rac1 has been identified as a key regulator of cancer cell invasion (6)(7)(8). C6 glioma cells with high Rac1 activity possess increased invasiveness compared with those with low Rac1 activity (19), indicating a favorable role for Rac1 in glioma invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 has been identified as a key regulator of cancer cell invasion (6)(7)(8). C6 glioma cells with high Rac1 activity possess increased invasiveness compared with those with low Rac1 activity (19), indicating a favorable role for Rac1 in glioma invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is one of the most studied Rho GTPase family members (5). Several lines of evidence indicate that Rac1 activation contributes to glioma cell invasion (6)(7)(8). Nakada et al (6) reported that the ephrin-B3 ligand facilitates the invasion of glioma cells through activation of Rac1.…”
Section: Introductionmentioning
confidence: 99%
“…It plays crucial roles in signal transduction pathway that control proliferation, adhesion, and migration of cells during embryonic development, invasiveness of tumour cells (Jin et al, 2007) as well as apoptosis (Sun et al, 2006). The expression of RAC1 is important for cell growth, motility and morphology in glioma cells (Hu et al, 2009;Moniz et al, 2013). Blockade of RAC1 signalling in tissue remodelling promotes the accumulation of type I collagen due to decreased collagenase activity (Igata et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Arf6 also has a clear role in cortical cytoskeleton rearrangement (5). This is strongly supported by evidence of Arf6 and Rac1 (Ras-related C3 botulinum toxin substrate) interplay (6), exemplified by Arf6 recruitment of the Rac1 GEF Kalirin, Arf6 promotion of Rac1 activation, and lamellipodia formation (7)(8)(9).…”
mentioning
confidence: 84%